Analysis of Blade Quantity Variations on Horizontal Axis Wind Turbine Type Taperless Airfoil SG6043 Using Blade Element Momentum (BEM) - Pratama Ricky Novianto; Fahrudin Fahrudin; Damora Rhakasywi; Tatik Juwairiyah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The design of taperless blades using the SG6043 Airfoil with different blade quantities through BEM simulation method is expected to serve as a reference for determining the design that yields the best operational efficiency. Simulation results show that the highest Cp value for the Taperless blade design is achieved with a variation of 3 wind turbine blades, resulting in a Cp value of 0.45 in the BEM simulation. The highest Cp value for the Taperless blade design with 4 wind turbine blades is 0.48 in the BEM simulation. Meanwhile, the highest Cp value for the Taperless blade design with 5 wind turbine blades is 0.47 in the BEM simulation. For low TSR values within the range of 1-4, turbines with 5 blades perform the best among various blade quantity variations, resulting in the highest Cp value. On the other hand, for high TSR values within the range of 5-10, turbines with the fewest blades, specifically 3 blades, achieve the highest Cp value.